2019
DOI: 10.1016/j.heliyon.2019.e01660
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of thyroid dysfunction by magnesium in experimental diabetes may also prevent diabetes-induced renal impairment

Abstract: Background Diabetes mellitus has been reported to cause thyroid dysfunction, which may also impair renal function. Magnesium has been reported to exert ameliorative effects in diabetes mellitus. This study investigated thyroid and renal functions in experimental type-2-diabetic Wistar rats. Methods Experimental type-2-diabetes was induced using short duration high-fat (30%) diet feeding followed by single-dose streptozotocin (35 mg/kg i.p.). Fifty rats were randomly div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
(37 reference statements)
1
6
0
1
Order By: Relevance
“…A preclinical study of cardiac failure and myocardial infarction (MI) has demonstrated that metformin expands the resilience of the heart to ischemia–reperfusion damage and, after infarction, diminishes the advancement of heart failure . The UK Prospective Diabetes Study (UKPDS) showed that metformin beneficially affects diverse cardiovascular hazard factors . Metformin treatment resulted in a 30% lower risk of macrovascular diseases contrasted with the other treatment modalities in the UKPDS .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A preclinical study of cardiac failure and myocardial infarction (MI) has demonstrated that metformin expands the resilience of the heart to ischemia–reperfusion damage and, after infarction, diminishes the advancement of heart failure . The UK Prospective Diabetes Study (UKPDS) showed that metformin beneficially affects diverse cardiovascular hazard factors . Metformin treatment resulted in a 30% lower risk of macrovascular diseases contrasted with the other treatment modalities in the UKPDS .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The UK Prospective Diabetes Study (UKPDS) showed that metformin beneficially affects diverse cardiovascular hazard factors. 11,12 Metformin treatment resulted in a 30% lower risk of macrovascular diseases contrasted with the other treatment modalities in the UKPDS. 13,14 For MI alone, the metformin group had a 42% lesser chance than the traditional treatment group.…”
Section: Introductionmentioning
confidence: 99%
“…AFE has a hypoglycemic effect in normal and diabetic mice [7]. Hyperglycemia usually accompanies the increased thyroid-stimulating hormone (TSH), triiodothyronine, and thyroxine levels [74]. AFE suppresses PD-L1 expression in the normal serum culture condition, which contains thyroid hormone and steroid hormones.…”
Section: The Balance Between Herbal Medicines and Hormones In Pd-l1 Ementioning
confidence: 99%
“…Доказана лечебно-терапевтическая роль магния при повреждении ЩЖ. Так, выявлено, что пероральное введение магния способно вызывать частичное восстановление функции ЩЖ у экспериментальных крыс с диабетом 2-го типа [20].…”
Section: а бunclassified